Dinamika Penghimpunan Zakat : Peluang dan Tantangan di LAZISMU - Nurul Azwani (Indonesia Journal of Zakat and Waqf, 2024)
This study aims to analyze the effectiveness of zakat collection at the Muhammadiyah Zakat Management Institution (LAZISMU) Pinrang District Service Office, as well as to identify opportunities and challenges faced in the process. The method used is a qualitative approach with field research based on phenomenology. Data was collected through observation, in-depth interviews with managers, staff, and donors of LAZISMU, as well as document analysis. The results of the study indicate that zakat fund collection at LAZISMU Pinrang District has increased from 2022 to 2023, supported by strategies such as socialization, utilization of social media, zakat pickup services, and bank transfers. However, the effectiveness of fund collection still faces challenges such as limited human resources, lack of public understanding about zakat, and the tendency of zakat contributors to distribute zakat directly to beneficiaries. Efforts to address these issues include enhancing outreach, increasing and improving the quality of human resources, and building public trust to channel zakat through LAZISMU. The implications of this study emphasize the importance of continuous education for the public on zakat distribution through trusted institutions and enhancing the capacity of human resources at LAZISMU to optimize zakat fund collection and management. These findings can serve as a foundation for LAZISMU and other zakat institutions in designing more effective zakat fund collection strategies to enhance community welfare.